Characterization of an 18,166 EST dataset for cassava (Manihot esculenta Crantz) enriched for drought responsive genes - Lokko, Y.; Anderson, J.; Rudd, S.; Raji, A.; Horvath, D.; Mikel, M.A.; Kim, R.; Liu, L.; Hernández, A.; Dixon, A.; Ingelbrecht, I.L. (Springer, 2007)
Cassava (Manihot esculenta Crantz) is a staple food for over 600 million people in the tropics and sub-tropics and is increasingly used as an industrial crop for starch production. Cassava has a high growth rate under optimal conditions but also performs well in drought-prone areas and on marginal soils. To increase the tools for understanding and manipulating drought tolerance in cassava, we generated expressed sequence tags (ESTs) from normalized cDNA libraries prepared from dehydration stressed and control well-watered tissues. Analysis of a total of 18,166 ESTs resulted in the identification of 8,577 unique gene clusters (5,383 singletons and 3,194 clusters). Functional categories could be assigned to 63% of the unigenes, while another 11% were homologous to hypothetical genes with unclear functions. The remaining ~26% were not significantly homologous to sequences in public databases suggesting that some may be novel and putatively specific to cassava. The dehydration-stressed library uncovered numerous ESTs with recognized roles in drought-responses, including those that encode late-embryogenesis-abundant proteins thought to confer osmoprotective functions during water stress, transcription factors, heat-shock proteins as well as proteins involved in signal transduction and oxidative stress. The unigene clusters were screened for short tandem repeats for further development as microsatellite markers. A total of 592 clusters contained 646 repeats, representing 3.3% of the ESTs queried. The ESTs presented here are the first dehydration stress transcriptome of cassava and can be utilized for the development of microarrays and gene-derived molecular markers to further dissect the molecular basis of drought tolerance in cassava.